Malocclusion and self-esteem of fourth year high school students of Commonwealth High School Academic Year 2013-2014. - Laroco, Maria Cecilia Y.
INTRODUCTION: It has been conceptualized that the first impression a person makes is based on his appearance which lasts for a long time and that the teeth is perceived to be an important part of the facial appearance. Having a good physical appearance has a positive effect on an individual's self-esteem. Based on such findings, most orthodontists consider having an aesthetic dental appearance. Would lead to a greater self-esteem and social well-being. The aim of this study is to determine whether there is a positive or negative correlation between malocclusion and self-esteem.